Dark consequences of social media-induced fear of missing out (FoMO): Social media stalking, comparisons, and fatigue - Tandon Anushree; Dhir Amandeep; Talwar Shalini; Kaur Puneet; Mäntymäki Matti (Elsevier, 2022)
Research on the dark side of social media usage has explored the fear of missing out (FoMO), social media fatigue (fatigue), social media stalking (stalking), and online social comparison (social comparison) independently. Accordingly, the complex interrelationships among these phenomena have remained understudied, creating a chasm that hinders a clearer understanding of their drivers and the potential counterstrategies to mitigate the collateral damage they may cause. We attempt to bridge this gap by drawing upon the theory of social com-parison and the theory of compensatory internet use to formulate a framework that hypothesizes the mechanism of interaction among these negative fallouts. The model, tested through analysis of data collected from 321 social media users from the United Kingdom (UK), takes into consideration the moderation effect of the frequency of posting social media status updates and social media envy, along with the mediation effect of social comparison and  stalking. The  results indicate that  FoMO and  social comparison are  directly associated with fatigue. Furthermore, social comparison partially mediates the association of FoMO and fatigue, while social media envy negatively moderates the association of FoMO with social comparison. The results provide new insights into the dynamic interplay of these dark side manifestations of social media.